The Legal Protection of the Family in Egyptian Law (Analytical Study) (in the Areas of Social Security, Social Insurance, Work, and Nationality) - Arafa, Prof. Dr. Muhammad Al-Sayed (Journal of Legal and Political Studies, 2018)
This research deals with the subject of legal protection of the family in Egyptian law (analytical study). The first section deals with the question of the legal protection of the family in terms of defining the meaning of the term "family", the term "legal protection of the family" and "the basis of family protection in the Arab Republic of Egypt". In the Islamic law and the Constitution, and the international conventions and conventions that it has signed in the field of family protection. The second section deals with the substantive protection of the family in the Egyptian legal system in the areas of social security, social security, maternity and childhood, employment and nationality, both in terms of protecting the child's right to nationality and protecting the rights of a foreign woman married to an Egyptian citizen. In the area of nationality. The third section deals with the procedural protection of the family in the Egyptian Code of Procedures, the Code of Civil and Commercial Proceedings, the Code of Criminal Procedure, the special protection of children and women when making claims for maintenance or custody, or when investigating and prosecuting them. The conclusion of the research includes a set of conclusions and recommendations reached by the researcher, including the importance of activating the penalties provided by the Labor Law regarding violations that may occur from some employers and the consequent reduction of the rights of women and minors related to motherhood and childhood.
Keywords: legal protection; Constitution; International Conventions; nationality